Hubungan Pengetahuan Kesehatan Prakonsepsi dengan Hasil Skrining Aplikasi ELSIMIL Pada Calon Pengantin - Trisnanda Marintan; Rozi Sastra Purna; Hudila Rifa Karmia (LPPM Hang Tuah Pekanbaru, 2024)
Stunting is a condition of growth failure in children with short bodies that do not match their developmental age, the cause of which can be identified from the preconception period through the ELSIMIL application screening. The research aimed to determine the relationship between preconception health knowledge and the results of ELSIMIL application screening for prospective brides and grooms. Cross-sectional research design with a sample of 106 prospective bride and groom respondents who were recorded as having applied ELSIMIL in three sub-districts of Padang City (Koto Tangah, Padang Timur, and Padang Selatan). The research was conducted from January-May 2024 and the analysis techniques were univariate, bivariate (chi-square test), and multivariate (multiple logistic regression test). The results of the analysis show that there is a relationship between preconception health knowledge (p=0.000), employment (p=0.001), and income (p=0.003) and there is no relationship between education (p=0.432) and the results of the ELSIMIL application screening as well as the most dominant factor. related is preconception health knowledge with an OR value of 13.754. This research concludes that preconception health knowledge is the main factor influencing ELSIMIL application screening results for prospective brides and grooms.